International Consensus for the Dosing of Corticosteroids in Childhood‐Onset Systemic Lupus Erythematosus With Proliferative Lupus Nephritis. Issue 2 (4th January 2022) - Chalhoub, Nathalie E.; Wenderfer, Scott E.; Levy, Deborah M.; Rouster‐Stevens, Kelly; Aggarwal, Amita; Savani, Sonia I.; Ruth, Natasha M.; Arkachaisri, Thaschawee; Qiu, Tingting; Merritt, Angela; Onel, Karen; Goilav, Beatrice; et al.
Abstract : Objective: To develop a standardized steroid dosing regimen (SSR) for physicians treating childhood‐onset systemic lupus erythematosus (SLE) complicated by lupus nephritis (LN), using consensus formation methodology. Methods: Parameters influencing corticosteroid (CS) dosing were identified (step 1). Data from children with proliferative LN were used to generate patient profiles (step 2). Physicians rated changes in renal and extrarenal childhood‐onset SLE activity between 2 consecutive visits and proposed CS dosing (step 3). The SSR was developed using patient profile ratings (step 4), with refinements achieved in a physician focus group (step 5). A second type of patient profile describing the course of childhood‐onset SLE for ≥4 months since kidney biopsy was rated to validate the SSR‐recommended oral and intravenous (IV) CS dosages (step 6). Patient profile adjudication was based on majority ratings for both renal and extrarenal disease courses, and consensus level was set at 80%. Results: Degree of proteinuria, estimated glomerular filtration rate, changes in renal and extrarenal disease activity, and time since kidney biopsy influenced CS dosing (steps 1 and 2). Considering these parameters in 5, 056 patient profile ratings from 103 raters, and renal and extrarenal course definitions, CS dosing rules of the SSR were developed (steps 3–5). Validation of the SSR for up to 6 months post–kidney biopsy was achieved with 1, 838 patient profile ratings from 60 raters who achieved consensus for oral and IV CS dosage in accordance with the SSR (step 6). Conclusion: The SSR represents an international consensus on CS dosing for use in patients with childhood‐onset SLE and proliferative LN. The SSR is anticipated to be used for clinical care and to standardize CS dosage during clinical trials.